Chicho’s adaptations of Poe: in search for an audience for terror (in television) - Roas, David (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The goal of my article is to study the adaptations of short stories by Edgar Allan Poe that Chicho Ibáñez Serrador made in the TV program Historias para no dormir (1966-1968). I must point out that my work does not rest on a classic vision of adaptation in what refers to the comparative analysis of works to determine their degree of fidelity, thematic, argumentative and formal modifications, etc. My objective is to analyze the way in which Chicho transferred Poe’s fantastic and terrifying poetics to television, showing how the director —determined by that massive audience and not yet accustomed to such genres (in that medium)— use certain plots, settings and themes, and how this decisively influenced the means of creation and reception of the fantastic and terror in Spanish audiovisual production.